Mathematical modeling of the two-phase fluid flow in inhomogeneous fractured porous media using the double porosity model and finite element method - V.I. Vasilyev; M.V. Vasilyeva; A.V. Grigorev; G.A. Prokopiev (Учёные записки Казанского университета: Серия Физико-математические науки)
Numerical simulation of the two-phase fluid flow in a fractured porous media using the double porosity model with a highly inhomogeneous permeability coefficient has been studied. A system of equations has been presented for the case of two-phase filtration without capillary and gravitational effects, which is a connected system of equations for pressure and saturation in a porous medium that contains a system of cracks. Different variants of specifying the flow functions between the porous medium and cracks have been considered. The numerical implementation for velocity and pressure approximation is based on the finite element method. To discretize the saturation equation, the classical Galerkin method with counter-flow approximation has been used. The results of numerical calculations for the model problem using various interflow functions have been presented.